2019
DOI: 10.1039/c8lc01053f
|View full text |Cite
|
Sign up to set email alerts
|

Natural gas vaporization in a nanoscale throat connected model of shale: multi-scale, multi-component and multi-phase

Abstract: Production of hydrocarbons from shale is a complex process that necessitates the extraction of multi-component hydrocarbons trapped in multi-scale nanopores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…For example, it has been experimentally proven that phase transition in confined space occurs isothermally at a lower pressure, or isobarically at a higher temperature, than that in the bulk phase. Recently, the critical point of pure fluids in confined space has also been unambiguously demonstrated to locate at a lower temperature and pressure than that in bulk by us using an isochoric cooling method . Experimental studies on the phase behavior of confined mixtures, on the other hand, are relatively scarce in the literature, not to mention the fact that their phase behavior in the critical region has never been experimentally explored, which, in turn, results in disagreement and conflicting conclusions about the pore critical point (PCP) of mixtures in confinement; PCP is defined as a point beyond which the condensation of confined fluids can no longer occur. Therefore, the purpose of this work is to verify its existence and demonstrate its shift from the bulk critical point.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been experimentally proven that phase transition in confined space occurs isothermally at a lower pressure, or isobarically at a higher temperature, than that in the bulk phase. Recently, the critical point of pure fluids in confined space has also been unambiguously demonstrated to locate at a lower temperature and pressure than that in bulk by us using an isochoric cooling method . Experimental studies on the phase behavior of confined mixtures, on the other hand, are relatively scarce in the literature, not to mention the fact that their phase behavior in the critical region has never been experimentally explored, which, in turn, results in disagreement and conflicting conclusions about the pore critical point (PCP) of mixtures in confinement; PCP is defined as a point beyond which the condensation of confined fluids can no longer occur. Therefore, the purpose of this work is to verify its existence and demonstrate its shift from the bulk critical point.…”
Section: Introductionmentioning
confidence: 99%
“…These properties in turn influence fluid entrainment and flow behavior in porous media. In this context, deviations in the bubble points of binary hydrocarbon mixtures shown experimentally using pressure–volume observations are relevant. Studies of natural gas vaporization in a nanoscale throat-connected model showed that the bubble point occurred at a lower pressure in the nanochannels than in the larger channels . Further, pores that are 10 nm or smaller in size were shown to greatly impact production from larger pores.…”
Section: Phase Transition Of Confined Liquidsmentioning
confidence: 99%
“…243−246 Studies of natural gas vaporization in a nanoscale throat-connected model showed that the bubble point occurred at a lower pressure in the nanochannels than in the larger channels. 247 Further, pores that are 10 nm or smaller in size were shown to greatly impact production from larger pores. Bubble points of propane− butane mixtures in nanochannels were significantly suppressed and under certain conditions were below the dew points of bulk mixtures.…”
Section: Phase Transitions Of Confined Hydrocarbonsmentioning
confidence: 99%
“…While the capital cost of microfluidic setup may be comparable to that of some conventional testing such as coreflood, the inherent speed and very low sample volume usage of microfluidic approaches derive their operational cost significantly lower than that of conventional methods. The precedent for microfluidic reservoir fluid analysis includes measurements of saturation point measurements, solubility, , diffusivity, , solid deposition, rheology, and nanoconfined fluid properties. Microfluidics has also been extended to probe the pore-scale dynamics of various enhanced oil recovery processes for conventional and unconventional reservoirs. Specifically for foam processes, a microfluidic device with different channel geometries (representative of SAGD reservoirs) was used to investigate the water–gas foam formation and fragmentation . The hysteresis of the foam generation and collapse has been evaluated and quantified as a function of gas/liquid volumetric ratio in a simple microfluidic channel .…”
Section: Introductionmentioning
confidence: 99%